A multi-objective approach to analyse the effect of fuel consumption on ship routing and scheduling problem. (17th April 2019) - Pratap, Saurabh; Zhang, Mengdi; Shen, Christopher L.D.; Huang, George Q.
This paper investigates the impact of fuel consumption on ship routing and scheduling problem. In current trends, the anthropogenic emission due to excess fuel consumption is a topic of intense debate in the global world ship trading society. We have modelled a problem as a mixed integer nonlinear programming (MINLP), which encounters the issues related to routing, fuel consumption, and customer demand. A meta-heuristic approach controlled elitist non-sorting genetic algorithm (CENSGA) has been proposed to solve the bi-objective problem. Finally, the utility of the model is demonstrated by a case study.